Reduced specificity of Erns antibody ELISAs for samples from piglets with maternally derived antibodies induced by vaccination of sows with classical swine fever marker vaccine CP7_E2alf. Issue 2 (4th January 2018) - Meyer, D.; Loeffen, W.; Postel, A.; Fritsche, S.; Becher, P.
Summary: Successful implementation of marker vaccines against classical swine fever virus is dependent on a reliable accompanying diagnostic assay that allows differentiation of infected from vaccinated animals (DIVA) as well as the development of a testing scheme during emergency vaccination. In this context, special attention needs to be paid to breeding farms, because the offspring of marker vaccinated sows possess maternally derived antibodies (MDAs). So far, limited information is available on the influence of MDAs on serological testing in the context of a DIVA strategy. Therefore, two commercially available E rns antibody ELISAs were compared, using serum samples of piglets with a high‐to‐moderate titre of MDAs against marker vaccine CP7_E2alf. False‐positive results were detected by both E rns antibody ELISAs for serum samples of piglets with an age of up to 4 weeks. Interestingly, most samples tested false‐positive in the first E rns antibody ELISA were identified correctly by the other E rns antibody ELISA and vice versa. In conclusion, in case of emergency vaccination of sows, the specificity of both ELISAs in newborn piglets younger than 4 weeks may be relatively low. This could be addressed in a testing strategy by either not sampling piglets up to the age of 4 weeks or using both ELISAs in a screening‐confirmation set‐up.